Salib Kasih : Tanggung Jawab Ekumenis Gereja Mengembangkan Eco-Tourism di Siatas Barita (Jurnal Pendidikan Agama dan Teologi, 2024)
This article discusses the role of the church in its ecumenical responsibility to support the development of eco-tourism in the Salib Kasih area, Siatas Barita. With the increasing awareness of the importance of environmental preservation, the church has the potential to become an agent of change through innovation and creativity. Factors contributing to the decline in visitor numbers, such as poor cleanliness, limited public facilities, and low creativity in tourism product development, are identified as the main challenges. Through collaboration between the church and the government, as well as the implementation of effective strategies, this area is expected to develop into a sustainable tourist destination that benefits the local community.